Interoperability assessment of open source BIM software for documenting architectural heritage in the chapel of San Pedro de Challapampa, Peru - Villegas Abrill, Jorge (2025)
The Chapel of San Pedro de Challapampa, an example of 16th-century Renaissance architecture, combines local techniques and Hispanic models from the Peruvian highlands. Declared a cultural heritage site in 1972, it has undergone interventions in 1974, 2002, 2014, and 2023. This study assesses the use of open source BIM software for documenting the building with an HBIM approach, analyzing the software's capability in the building's record. The methodology employed was the analysis of use cases under a data exchange conformity test approach in IFC format. Despite limitations with specific IFC classes, key elements were recorded, and alterations in the building were identified. The study concludes that the information was interoperable, being imported into other IFC reading programs, and that the model facilitates analysis and decision-making for building management. However, further studies are required to evaluate the software's effectiveness.